Transient population dynamics impede restoration and may promote ecosystem transformation after disturbance - Shriver, Robert K.; Andrews, Caitlin M.; Arkle, Robert S.; Barnard, David M.; Duniway, Michael C.; Germino, Matthew J.; Pilliod, David S.; Pyke, David A.; Welty, Justin L.; Bradford, John B.; Wang, Shaopeng (Ecology letters, 2019)
The apparent failure of ecosystems to recover from increasingly widespread disturbance is a global concern. Despite growing focus on factors inhibiting resilience and restoration, we still know very little about how demographic and population processes influence recovery. Using inverse and forward demographic modelling of 531 post‐fire sagebrush populations across the western US, we show that demographic processes during recovery from seeds do not initially lead to population growth but rather to years of population decline, low density, and risk of extirpation after disturbance and restoration, even at sites with potential to support long‐term, stable populations. Changes in population structure, and resulting transient population dynamics, lead to a > 50% decline in population growth rate after disturbance and significant reductions in population density. Our results indicate that demographic processes influence the recovery of ecosystems from disturbance and that demographic analyses can be used by resource managers to anticipate ecological transformation risk.